PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN TIM BOLA BOLA BASKET PUTRI SMA NEGERI 1 SIAK - Lisa Purnama; Slamet Slamet; Alimandan Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on information with coach and field observation that the female basketball team at SMA Negeri 1 Siak is still not maximal in mastering the game of basketball. As well as the researcher saw that the physical condition of the SMA Negeri 1 Siak team was still far from expected, this was evident from almost every participation in the Siak 1 High School basketball team championship often experienced a decrease in physical conditions such as endurance when the competition. This can be seen from the matches that were held during the 4 quarters. In the 3 quarter the shots were not good, so many balls went off both in the freethrow and the three points. Then, in quarter 4 you get a penalty of free throw 3-4 times, and can only to enter the ball into the ring 2 times. The purpose of this research was to determine the effect of circuit training on the endurance of the girl’s basketball team at SMA Negeri 1 Siak. The population in this study amounted to 15 people consist of the girl’s group. Sampling was determined by taking the entire population as a sample (total sampling). This research instrument used a 15 minutes run Balke test. The analysis technique used the t-test. Based on the t-test produces a tcount of 2.574 with a ttable of 1.762, so Ha is rejected, at the alpha (α) 0.05 level. It can be concluded that there is a significant effect of circuit training on the endurance of the SMA Negeri 1 Siak basketball team.Key Words: Circuit Training, Endurance